EFFECT OFAN AWARENESS PROGRAM ON KNOWLEDGE OF PHYSIOTHERAPY INTERVENTION REGARDING URINARY INCONTINENCE AMONG PREMENOPAUSAL WOMEN. (Cuestiones de Fisioterapia, 2025)
Background: Urinary Incontinence (UI) is a prevalent and often debilitating condition characterized by the involuntary loss of urine, which can significantly impact an individual's quality of life and psychological wellbeing. There is a pressing need for targeted awareness initiatives aimed at dispelling myths, reducing stigma, and empowering individuals to seek timely intervention for UI. In light of this imperative, the present research endeavours to investigate the effectiveness of an awareness program on knowledge of physiotherapy interventions regarding UI among premenopausal women